Olivine - Science History Institute (2017)
Olivine is a mineral with a distinct green color and granular-shaped crystals. It is one of the first minerals to cool and crystallize from magma. Recently, olivine has been used as an alternative to silica sand and quartz sand in metal casting and sandblasting.
Keywords: Precious stones; Minerals; Olivine